Discovery of potent and selective reversible Bruton's tyrosine kinase inhibitors. (15th June 2021) - Qiu, Hui; Ali, Zahid; Bender, Andrew; Caldwell, Richard; Chen, Yi-Ying; Fang, Zhizhou; Gardberg, Anna; Glaser, Nina; Goettsche, Anja; Goutopoulos, Andreas; Grenningloh, Roland; Hanschke, Bettina; et al.
Graphical abstract: Abstract: Bruton's tyrosine kinase (BTK) is a cytoplasmic, non-receptor tyrosine kinase member of the TEC family of tyrosine kinases. Pre-clinical and clinical data have shown that targeting BTK can be used for the treatment for B-cell disorders. Here we disclose the discovery of a novel imidazo[4, 5- b ]pyridine series of potent, selective reversible BTK inhibitors through a rational design approach. From a starting hit molecule 1, medicinal chemistry optimization led to the development of a lead compound 30, which exhibited 58 nM BTK inhibitory potency in human whole blood and high kinome selectivity. Additionally, the compound demonstrated favorable pharmacokinetics (PK), and showed potent dose-dependent efficacy in a rat CIA model.